Paradise - Morrison, Toni. (London : Vintage, 1999)
Four young women living in a convent near Ruby, Oklahoma, are viciously attacked in 1976 after residents become convinced the women are the source of the problems that have been sweeping the exclusively African-American community.
Adult.
Keywords: African Americans -- Oklahoma -- Fiction; Convents -- Oklahoma -- Fiction; Women -- Oklahoma -- Fiction; African Americans -- Oklahoma -- Fiction; Convents -- Fiction; Women -- Oklahoma -- Fiction; Oklahoma -- Fiction; Oklahoma -- Fiction